2010
DOI: 10.1038/pj.2010.44
|View full text |Cite
|
Sign up to set email alerts
|

Resistive–conductive transitions in the time-dependent piezoresponse of PVDF-MWCNT nanocomposites

Abstract: Nanocomposites were prepared by melt blending of multiwalled carbon nanotubes (MWCNTs) filled with polyvinylidene fluoride. Time-dependent piezoresistance was investigated as a function of concentration. In the quasi-static case, a transition from negative pressure coefficient to positive pressure coefficient (PPC) behavior was observed. The PPC effect was negligible at high concentrations. At short times, the resistive response decreased for all nanocomposites, with the magnitude of the decrease proportionate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 35 publications
(49 reference statements)
0
11
0
Order By: Relevance
“…30, 31 However, superior hydrophobic piezoelectric PVDF coating method, which contains high β – phase content and increased contact angle, are barely reported. Currently some researchers indicated that the induction of nanomaterials could increase the surface roughness and also derive the α – phase of PVDF to β – crystal formation during a chain alignment caused by the electrostatic interaction between the methylene and charged nanoparticles 32-36 . The zigzag carbon atoms on the carbon nanotubes (CNTs) surface could induce β – phase formation during the crystallization of PVDF 37-39 and π conjugated structure of CNTs will attract the F- to CNTs surface.…”
Section: Introductionmentioning
confidence: 99%
“…30, 31 However, superior hydrophobic piezoelectric PVDF coating method, which contains high β – phase content and increased contact angle, are barely reported. Currently some researchers indicated that the induction of nanomaterials could increase the surface roughness and also derive the α – phase of PVDF to β – crystal formation during a chain alignment caused by the electrostatic interaction between the methylene and charged nanoparticles 32-36 . The zigzag carbon atoms on the carbon nanotubes (CNTs) surface could induce β – phase formation during the crystallization of PVDF 37-39 and π conjugated structure of CNTs will attract the F- to CNTs surface.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the growing interest in polymers from renewable resources, the importance of multifunctionality from the polymers has grown especially in the field of polymer sensors [14, 15]. The discovery of carbon nanotubes by Iijima in 1991 [16] has resulted in designing novel materials with extraordinary materials with extraordinary combination of mechanical, thermal, and electrical properties [17, 18].…”
Section: Introductionmentioning
confidence: 99%
“…The authors can only hypothesize about the possible source of the noise. The experimental observations from the previous authors' work demonstrated that the effective area for tunneling conduction, A, is modified by the applied stress [19]; see Equation (7). If σ is held constant for an extended period of time, the authors believe that A fluctuates in a random fashion, thus, causing the noise in Figure 9.…”
Section: Trimming the Offset Resistances For R 1 = Rmentioning
confidence: 99%
“…By taking a glance at the datasheets of commercial FSRs [11][12][13], they exhibit from ten to one hundred times more drift and hysteresis error than load cells. Fortunately, a great effort is currently placed on improving the performance of FSRs by investigating multiple trends such as the integration of carbon nanotubes in the polymer matrix [7,14], changing the electrode configuration of the assembled sensor [15,16], testing different types of polymers [17,18], and adding non-conductive nanoparticles to reinforce the polymer matrix with the aim of reducing creep [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation